A Review on Shwasahara Dravyas in Bhavaprakash Nighantu - Kailash Rana; Ashwani Upadhyaya; Navneet Sharma; Rashmi Srivastava; Chandni Gupta; Ram Deo Pandit (International Journal of Ayurveda and Pharma Research, 2023)
Respiratory disorders (Shwasa Roga) and coughs are global health complaints that affect everyone differently throughout their lives. These complaints are prevalent across all age groups. Dyspnea (shortness of breath) caused by respiratory dysfunction is classified under Shwasa Roga in Ayurveda. Exposure to dust, smoke and environmental variations are the main risk factors for this disorder. Bhavaprakasha Nighantu is one of the foundational texts of Ayurveda. It contains descriptions of Dravyas which are indicated for various diseases and also Shwasahara Dravyas. In this review article, an extensive search of drugs for Shwasa Roga, in Bhavaprakasha Nighantu is done. The study showed that out of 23 Vargas of drugs in Bhavaprakasha Nighantu, 18 Vargas contain 92 Dravyas for Shwasa of plants, animals, and minerals origin.